An effective technique in treatment of femoral neck fractures - ostheosynthesis under double fluoroscopic guidance - Gülenç, Barış; Günaydın, Burak; Çamur, Savaş; Talmaç, Mehmet Ali; Güler, Yasin; Kara, Adnan (NLM (Medline), 2019)
PURPOSE OF THE STUDY The most commonly used technique for fixation of the femoral neck fractures is percutaneous osteosynthesis with cannulated screw under fluoroscopy guidance. Osteosynthesis performed under single-fluoroscopic guidance requires continuous repositioning the fluoroscope to obtain biplane imaging. This study aimed to evaluate whether there is a statistically significant difference between the osteosynthesis procedures performed under guidance of single-fluoroscopy and double fluoroscopy with respect to radiation emission safety and treatment parameters for fixation of femoral neck fractures. MATERIAL AND METHODS This retrospective study included 35 patients operated for femoral neck fracture between December 2013 and October 2017. Osteosynthesis was performed in 21 of these patients using cannulated screw under guidance of single-fluoroscopy whereas other 14 patients underwent same type of osteosynthesis assisted by double-fluoroscopy. The parameters of these two groups such as duration of surgery preparation, duration of the surgery, duration of radiation exposure, collo-diaphyseal angle and Harris hip score values were recorded. RESULTS No significant difference was found between the groups regarding time for surgery preparation (p > 0.05). On the other hand, duration of surgery and overall duration of radiation exposure were found 14 (p < 0.05) and 15 (p < 0.05) minutes shorter in the double-fluoroscopy group, respectively. No significant difference was found between the groups in terms of collo-diaphyseal angle and Harris hip score values (p > 0.05). CONCLUSIONS Use of double-fluoroscopy significantly reduces time of surgical duration and also level of radiation exposure in surgery of femoral neck fractures. Key words:double fluoroscopy, femoral neck fractures, radiation, osteosynthesis, cannulated screw.
Efektivní technika lé?ení zlomenin kr?ku femuru – osteosyntéza s vyu?itím zdvojené fluoroskopie
Keywords: Double Fluoroscopy; Femoral Neck Fractures; Radiation; Osteosynthesis; Cannulated Screw